2017
DOI: 10.1186/s12870-017-1078-3
|View full text |Cite
|
Sign up to set email alerts
|

GaMYB85, an R2R3 MYB gene, in transgenic Arabidopsis plays an important role in drought tolerance

Abstract: BackgroundMYB transcription factors (TFs) are one of the largest families of TFs in higher plants and are involved in diverse biological, functional, and structural processes. Previously, very few functional validation studies on R2R3 MYB have been conducted in cotton in response to abiotic stresses. In the current study, GaMYB85, a cotton R2R3 MYB TF, was ectopically expressed in Arabidopsis thaliana (Col-0) and was functionally characterized by overexpression in transgenic plants.ResultsThe in-silico analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(55 citation statements)
references
References 74 publications
(72 reference statements)
1
43
0
Order By: Relevance
“…TFs, as master regulators of many stress-responsive genes, are potential genomic candidates for enhancing tolerance to abiotic stresses such as drought because of their role in enabling plants to withstand unfavourable environments [12,69]. It is now well established that several TF families, including bZIP (mainly AREB/ABF), AP2/ERF, NAC, bHLH, WRKY, and MYB, are key regulators that participate in various abiotic stresses [5,[70][71][72]. Among AREB/ABF subfamily genes in Arabidopsis, the expression of four AREB/ABF TFs (ABF1, ABF3, AREB1/ABF2 and AREB2/ABF4) was induced by abiotic stresses in vegetative tissues; except for ABF1, the remaining TFs were significantly induced both by osmotic and ABA stresses such as dehydration, and ABF2 is also likely involved in glucose signalling [56,73,74].…”
Section: The Role Of Tfs In Response To Drought Stressmentioning
confidence: 99%
“…TFs, as master regulators of many stress-responsive genes, are potential genomic candidates for enhancing tolerance to abiotic stresses such as drought because of their role in enabling plants to withstand unfavourable environments [12,69]. It is now well established that several TF families, including bZIP (mainly AREB/ABF), AP2/ERF, NAC, bHLH, WRKY, and MYB, are key regulators that participate in various abiotic stresses [5,[70][71][72]. Among AREB/ABF subfamily genes in Arabidopsis, the expression of four AREB/ABF TFs (ABF1, ABF3, AREB1/ABF2 and AREB2/ABF4) was induced by abiotic stresses in vegetative tissues; except for ABF1, the remaining TFs were significantly induced both by osmotic and ABA stresses such as dehydration, and ABF2 is also likely involved in glucose signalling [56,73,74].…”
Section: The Role Of Tfs In Response To Drought Stressmentioning
confidence: 99%
“…Each bar shows the mean ± SE of triplicate assays. * or ** indicates a statistically significant difference relative to the value at 0 hr for each gene at p < .05 or .01, respectively involved in plant development and metabolism (Alonso-Peral et al, 2010;Sheldon et al, 2001) and response to pathogens and abiotic stress (Yang et al, 2014;Butt et al, 2017). Moreover, studies have revealed that MYB transcriptome factors participate in response to B. cinerea.…”
Section: F I G U R Ementioning
confidence: 99%
“…Furthermore, Yin et al [ 22 ] showed that OsMYBR1 that was isolated from Oryza sativa improves drought tolerance of transgenic plants through the up-regulation of stress-related genes and the accumulation of osmoprotectants. Similarly, Butt et al [ 23 ] demonstrated that GaMYB85 confers good drought tolerance in Gossypium arboreum , most probably via an ABA-induced pathway. Altogether, these evidences demonstrated the versatility and importance of this gene family in plants.…”
Section: Introductionmentioning
confidence: 98%